2019
DOI: 10.1038/s41593-019-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal somatostatin interneurons encode fear memory

Abstract: Theories stipulate that memories are encoded within networks of cortical projection neurons (PNs). Conversely, GABAergic interneurons (INs) are thought to function primarily to inhibit PNs and thereby impose network gain control, an important but purely modulatory role. Here we show in male mice that associative fear learning potentiates synaptic transmission and cue-specific activity of medial prefrontal cortex (mPFC) somatostatin interneurons (SST-INs), and that activation of these cells controls both memory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
142
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(169 citation statements)
references
References 55 publications
17
142
1
Order By: Relevance
“…As to be expected, the SOM cells within the PFC are involved in many functions; for example, some PFC SOM cells contribute to reading emotions (affective state discrimination) 52 , others encode fear memories 53 ; and locally opto-activating neocortical NOS1 and SOM cells increases cerebral blood flow 54,55 . The c-fosdependent activity-tagging technique allows the SOM/GABA cells that become activated by sleep deprivation to be highlighted from the other functions that these cells carry out.…”
mentioning
confidence: 78%
“…As to be expected, the SOM cells within the PFC are involved in many functions; for example, some PFC SOM cells contribute to reading emotions (affective state discrimination) 52 , others encode fear memories 53 ; and locally opto-activating neocortical NOS1 and SOM cells increases cerebral blood flow 54,55 . The c-fosdependent activity-tagging technique allows the SOM/GABA cells that become activated by sleep deprivation to be highlighted from the other functions that these cells carry out.…”
mentioning
confidence: 78%
“…Increasing L4 SOM-IN activity may decrease the activity of PV-INs, resulting in increased activity of excitatory neurons (Xu et al, 2013), and increased SOM-IN activity during learning has been reported earlier (Cummings and Clem, 2020;Cybulska-Klosowicz et al, 2013b).…”
Section: L4 Som-in Chemogenetic Excitation Does Not Influence Learninmentioning
confidence: 87%
“…Even in the absence of the brake, CeM is not active without an input from BA. BA receives afferent connections from LA and projects to the PL, the IL, and CeM (Courtin et al, 2014 ; Senn et al, 2014 ; Asede et al, 2015 ; McGarry and Carter, 2016 ; Cummings and Clem, 2020 ). The PL and IL, in turn, project back to BA (Vertes, 2004 ; Cho et al, 2013 ; Courtin et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PL and IL receive afferent connections from BA and project back to it (Vertes, 2004 ; Cho et al, 2013 ; Courtin et al, 2014 ; Bloodgood et al, 2018 ). To do this, the inhibitory control of parvalbumin interneurons of the mPFC, respectively the units PLpv in the PL and ILpv in the IL, must be removed through the activation of somatostatin interneurons, respectively PLs and ILs (Courtin et al, 2014 ; McGarry and Carter, 2016 ; Lucas and Clem, 2018 ; Cummings and Clem, 2020 ).…”
Section: Methodsmentioning
confidence: 99%